The economic burden of subjective cognitive decline, mild cognitive impairment and Alzheimer's dementia: excess costs and associated clinical and risk factors - Eva Gläser; Ingo Kilimann; Moritz Platen; Wolfgang Hoffmann; Frederic Brosseron; Katharina Buerger; Marie Coenjaerts; Emrah Düzel; Michael Ewers; Klaus Fliessbach; Ingo Frommann; Maria Gemenetzi; et al. (Alzheimer’s Research & Therapy, 2025)
Abstract Background With the availability of first disease-modifying treatments, evidence on costs across the entire Alzheimer's Continuum, especially for early disease stages, becomes increasingly important to inform healthcare planning, resource allocation, and policy decisions. This study assessed costs and cost-associated factors in patients with subjective cognitive decline (SCD), mild cognitive impairment (MCI) and Alzheimer's Disease (AD) dementia compared to healthy controls. Methods The German DELCODE cohort study assessed clinical data, healthcare resource use, and informal care provision. Costs were calculated from payer and societal perspectives using standardized unit costs, and multivariate regression analyses identified cost-associated factors. Results From a payer perspective, costs were elevated by 26% for SCD (adjusted mean 5,976€ [95%CI 4,598-7,355€]), 85% for MCI (8,795€ [6,200-11,391€]) and 36% for AD (6,454€ [2,796-10,111€]) compared to controls (4,754€ [3,586-5,922€]). Societal costs were elevated by 52% for SCD (adjusted mean 8,377€ [95%CI 6,009-10,746€]), 170% for MCI (14,886€ [9,524-20,248€]) and 307% for AD (22,481€ [9,994-34,969€]) compared to controls (5,522€ [3,814-7,230€]). APOE e4 negative patients showed higher costs compared to APOE e4 positive patients. Hypertension was associated with higher costs. Conclusions Healthcare costs are already elevated in early subjective and objective cognitive impairment, driven by formal and informal care. The study emphasizes the importance of early interventions to reduce the economic burden and delay progression.